The reverse revolving door in the supervision of European banks - Stefano Colonnello; Michael Koetter; Alex Sclip; Konstantin Wagner (Halle Institute for Economic Research (IWH), 2023)
We show that around one third of executive directors on the boards of national supervisory authorities (NSA) in European banking have an employment history in the financial industry. The appointment of executives without a finance background associates with negative valuation effects. Appointments of former bankers, in turn, spark positive stock market reactions. This 'proximity premium' of supervised banks is a more likely driver of positive valuation effects than superior financial expertise or intrinsic skills of former executives from the financial industry. Prior to the inception of the European Single Supervisory Mechanism, the presence of former financial industry executives on the board of NSA associates with lower regulatory capital and faster growth of banks, pointing to a more lenient supervisory style.
urn:nbn:de:gbv:3:2-1029909
Keywords: G14; G21; G28; 330; banking supervision; conflicts of interest; revolving door